Cellulose supported magnetic nanohybrids: Synthesis, physicomagnetic properties and biomedical applications-A review. (1st September 2021) - Haniffa, Mohamed Abdul Cader Mohamed; Munawar, Khadija; Chee, Ching Yern; Pramanik, Sumit; Halilu, Ahmed; Illias, Hazlee Azil; Rizwan, Muhammad; Senthilnithy, Rajendram; Mahanama, Kariyawasam Ranaweerage Ranjith; Tripathy, Ashis; Azman, Mohd Fahmi
Abstract: Cellulose and its forms are widely used in biomedical applications due to their biocompatibility, biodegradability and lack of cytotoxicity. It provides ample opportunities for the functionalization of supported magnetic nanohybrids (CSMNs). Because of the abundance of surface hydroxyl groups, they are surface tunable in either homogeneous or heterogeneous solvents and thus act as a substrate or template for the CSMNs' development. The present review emphasizes on the synthesis of various CSMNs, their physicomagnetic properties, and potential applications such as stimuli-responsive drug delivery systems, MRI, enzyme encapsulation, nucleic acid extraction, wound healing and tissue engineering. The impact of CSMNs on cytotoxicity, magnetic hyperthermia, and folate-conjugates is highlighted in particular, based on their structures, cell viability, and stability. Finally, the review also discussed the challenges and prospects of CSMNs' development. This review is expected to provide CSMNs' development roadmap in the context of 21st-century demands for biomedical therapeutics. Highlights: Cellulose utilization for the synthesis of magnetic nanohybrids is reviewed. The review presents various shapes of cellulose supported magnetic nanohybrids (CSMNs). Synthesis and physicomagnetic properties of different CSMNs are discussed. Advances in the biomedical applications of CSMNs are explicated. Challenges in preparation of CSMNs and future perspectives are expounded.